A general synthesis of aromatic amides via palladium-catalyzed direct aminocarbonylation of aryl chlorides. Issue 9 (29th March 2022) - Wang, Peng; Yang, Ji; Sun, Kangkang; Neumann, Helfried; Beller, Matthias
Abstract : Aryl amines made easy by palladium-catalyzed aminocarbonylation of aryl chlorides. Abstract : The direct palladium-catalyzed selective carbonylative coupling of less reactive aryl chlorides (including electron-rich, -neutral and -deficient ones) with primary and secondary aliphatic and aromatic amines is described for the first time. Key for the success of this transformation is the use of a palladium/Xantphos catalyst system in the presence of cesium chloride (CsCl) as additive. In general, this catalytic system allows for efficient conversion of diverse aryl chlorides with an array of amines and with good functional group compatibility (60 examples, conversion up to 99%, isolated yield up to 95%).